1992
DOI: 10.1111/j.1525-1594.1992.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Albumin Concentration of Supplementation Fluid for Double Filtration Plasmapheresis

Abstract: Until recently, the albumin concentration of supplementation fluid for double filtration plasmapheresis (DFPP) has been empirically determined. Inadequate albumin infusion often leads to hypoproteinemic symptoms such as edema. In the current study, an aimed condensation coefficient (CCaimed) was introduced in an attempt to estimate the appropriate plasma albumin level for each patient. This coefficient is theoretically derived from a one-compartment model for the patient's plasma albumin: CCaimed = CS/CD = 1 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…We considered this fact could prevent adverse effects, such as hypotension, internal shunt occlusion, fall down, etc., that was supposed to be related with intravascular dehydration due to the decrease of plasma oncotic pressure during DFPP treatment (Table 1). Mineshima et al also reported that inadequate infusion of albumin solution in DFPP treatment might lead to hypoproteinemic symptoms such as edema [11,12]. Like these patients' condition should be the hamper for the safety transplant operation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We considered this fact could prevent adverse effects, such as hypotension, internal shunt occlusion, fall down, etc., that was supposed to be related with intravascular dehydration due to the decrease of plasma oncotic pressure during DFPP treatment (Table 1). Mineshima et al also reported that inadequate infusion of albumin solution in DFPP treatment might lead to hypoproteinemic symptoms such as edema [11,12]. Like these patients' condition should be the hamper for the safety transplant operation.…”
Section: Discussionmentioning
confidence: 93%
“…Until now, albumin concentration as supplementation fluid was determined empirically in the each institution [4]. In our country from 7% to 8% albumin solution that was akin to the concentration of serum total protein has been normally used for DFPP treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Mineshima et al (5,6) introduced a theoretical model for albumin transport in the partially discarded DFPP to determine the optimum albumin concentration and optimum amount of the supplementation fluid base. The albumin SC value, however, is constant during the treatment in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, DFPP has no stringency for the subclass in removal and there is no limit to the volume that can be processed while the column does not clot; therefore, the conditions in which plasma adsorption is unsuitable can be the target of DFPP. However, DFPP cannot use FFP, which has a lower oncotic pressure than plasma, as a supplementary fluid because DFPP requires supplementary fluids with a higher oncotic pressure—usually an albumin solution with a concentration of about 10% (18). Substances with a low production rate can sometimes be decreased considerably during DFPP, as described above; therefore, patients with active bleeding, those expecting an operation, or those with active infections are appropriately treated using simple plasma exchange with FFP supplementation.…”
Section: Choice Of Modality With Consideration Of Complicationsmentioning
confidence: 99%